Microwave assisted synthesis of pyrimido[4,5-d]pyrimidine derivatives in dry media - Kategaonkar, A.H.; Sadaphal, S.A.; Shelke, K.F.; Shingate, B.B.; Shingare, M.S. (Інститут молекулярної біології і генетики НАН України, 2009)
Pyrimido[4,5-d]pyrimidine derivatives were synthesized by using an efficient, facile and solvent-free procedure. Here, a non-conventional synthetic procedure has been developed where solid support of alumina is used as energy transfer medium under microwave irradiation (MWI) which devoids hazards of solution phase reactions. The reaction time has been brought down from minutes to seconds with improved yield as compared to reported method.